PENERAPAN PROGRAM KESELAMATAN DAN KESEHATAN KERJA DAN KOMPENSASI: PENGARUHNYA TERHADAP KINERJA PETUGAS KEBERSIHAN DINAS KEBERSIHAN DAN PERTAMANAN KOTA DENPASAR - Camila Suartha, Angelica; Sintaasih, Desak Ketut (E-Jurnal Manajemen; Vol 4 No 9 (2015), 2015)
Occupational health and safety program and compensation are important aspects for the janitor to improve their performance. The purpose of this study was to investigate the application of occupational safety and health program and compensation as well as its influence on the performance of the janitor. Respondents in this study is 60 cleanness and landscaping Denpasar City. This study uses multiple linear regression analysis technique. The results showed there were implementation of occupational health and safety program and compensation is fair. Occupational health and safety program positive and significant impact on the performance of the janitor. These results can be interpreted that the better health and safety at work, the performance of the janitor is also getting better. Compensation is also positive and significant effect on the performance of the janitor. These results indicate the better application of the compensation the better the performance of the janitor who is under the auspices of the Department of cleanness and landscaping Denpasar City.
Keywords: Health and Safety, compensation, employee performance